Contribution to the Algal Flora (Chlorophyceae) of Namchi, Sikkim-Himalayas - Kumar, S.; Rai, S.K. (Our Nature, 2006)
The present communication is a part of survey being conducted to study the fresh water algal flora of Namchi, South Sikkim. Thirteen taxa of class Chlorophyceae, which include 8 genera, 10 species and 3 varieties, were identified from 6 samples. Spirogyra nitida (Dillw.) Link, Netrium digitus (Ehr.) Itzigs. and Roth. and Scenedesmus bijugatus (Turp.) Kuetz. were the dominant green algae followed by the remaining other rare species of Scenedesmus and Staurastrum. All these taxa constitute new records for the study area. Key words: Chlorophyceae, Fresh water algae, India, Namchi, Sikkim-Himalaya doi:10.3126/on.v3i1.334 Our Nature (2005) 3: 50-55